STRATEGI KONSEP TRI HITA KARANA: MENINGKATKAN PENGEMBANGAN PARIWISATA (RIVER TUBING) DI DESA PENATIH DANGIN PURI KECAMATAN DENPASAR TIMUR KOTA DENPASAR - I Kadek Aditya Gustaman; I Made Kartika; I Made Artayasa; Ida Bagus Yogi Pranaditha; Anak Agung Made Kariana; Rui Ximenes; Aditya Junio Wardhana; Imam Pambudi; Agus Teja Saputra (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2025)
This study aims to examine in depth the application of the Tri Hita Karana concept, encompassing harmony with God (Parahyangan), harmony with fellow human beings (Pawongan), and harmony with nature (Palemahan), as the foundation for river tubing tourism development strategies in Penatih Dangin Puri Village, East Denpasar District, Denpasar City. The research background is based on the potential of the region's rivers, which possess ecological, cultural, and economic value, yet their utilization as tourist destinations remains limited. Using a qualitative approach with participatory observation, in-depth interviews, and documentation studies, this study seeks to uncover how the philosophical values ​​of Tri Hita Karana are integrated into destination management, identify obstacles encountered, and formulate sustainable strategies based on local wisdom. The results indicate that the implementation of Tri Hita Karana provides an effective framework for strengthening tourism sustainability, particularly through strengthening community spirituality, social cohesion, and environmental conservation. However, significant challenges remain related to institutional management, limited resources, and low community participation. These findings underscore the importance of multi-stakeholder collaboration, capacity building for local human resources, and strengthening culturally based regulations as strategic steps to maximize the potential of river tubing in Penatih Dangin Puri Village.